Cocoa Flavanol Cardiovascular Effects Beyond Blood Pressure Reduction. Issue 4 (30th October 2015) - Jumar, Agnes; Schmieder, Roland E.
Abstract : The protective cardiovascular (CV) effect of cocoa flavanol has been a target of many recent clinical prospective and retrospective investigations. Epidemiological data in different patient cohorts revealed an association between higher intake of flavanol‐rich foods and decreased incidence of CV events, especially stroke and myocardial infarction. Cocoa flavanol has been shown to reduce systolic (2.8 mm Hg) and diastolic (2.2 mm Hg) office blood pressure (BP). Greater BP reduction has been found in hypertensive patients and people younger than 50 years. Cocoa flavanol intake exerts beneficial effects on pathophysiologic mechanisms of hypertension‐related organ damage, such as improved endothelial function, anti‐inflammatory potency, inhibition of platelet activation, and increased vasodilatory capacity. Recent clinical trials have focused on establishing a potential link between epidemiology and pathophysiology of flavanol and identified possible mechanisms for prevention of end‐organ damage in patients at CV risk. This review summarizes the available data on the antihypertensive effects of cocoa flavanol beyond BP‐BP lowering lowering effects, accentuates subgroup‐specific protective actions of cocoa according to patients' different CV risk profile, and outlines potential cocoa flavanol–associated clinical implications.